Houses in Transformation Search for the Implicit Reasons - Khan, Tareef Hayat (SpringerBriefs in Geography, 2014)
This book analyzes the reasons of spontaneous transformation in self-built houses in the context of developing countries. Recognizing Housing Transformation as a natural phenomenon, the book focuses on self-built houses in the city of Dhaka. Firstly, it explains the explicit reasons behind spontaneous housing transformations. Then the book carefully unveils the implicit values that are hidden behind those explicit reasons. The entire book is an ethnographic journey, which expresses unique stories behind houses in transformation.